2007
DOI: 10.1111/j.1365-2850.2007.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effectiveness of an educational intervention aimed at changing attitudes to self‐harm

Abstract: Nurses' attitudes toward service users who repeatedly self-harm can be negative and may interfere with the user's willingness to engage with services. The effectiveness of an educational intervention aimed at improving nurses' attitudes in this area was tested in this study. The intervention consisted of attendance on an accredited course on self-harm over a period of 15 weeks and the outcome of interest was attitudes as measured by the Self Harm Antipathy Scale. When deployed in a before-and-after design with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 8 publications
1
68
1
1
Order By: Relevance
“…Education programmes on self-harm have been developed and it is evident that a number of these programmes have a positive effect on nurses' self-reported attitudes towards self-harm (Holdsworth et al 2001, Patterson et al 2007, McAllister et al 2009, Kool et al 2014. Furthermore, there is a general assumption among researchers that the nursing care for patients who self-harm will improve as a result of positive changes in attitude (Patterson et al 2007, McAllister et al 2009). However, empirical evidence is lacking to support this assumption.…”
Section: Introductionmentioning
confidence: 91%
“…Education programmes on self-harm have been developed and it is evident that a number of these programmes have a positive effect on nurses' self-reported attitudes towards self-harm (Holdsworth et al 2001, Patterson et al 2007, McAllister et al 2009, Kool et al 2014. Furthermore, there is a general assumption among researchers that the nursing care for patients who self-harm will improve as a result of positive changes in attitude (Patterson et al 2007, McAllister et al 2009). However, empirical evidence is lacking to support this assumption.…”
Section: Introductionmentioning
confidence: 91%
“…Some suicide awareness training aims to change attitudes and promote intervention (Patterson 2007;Griesbach 2008) and there is evidence that even relatively minor interventions can prevent suicides (Fleischmann 2008). A literature review commissioned by the Scottish Government has called for more research into suicide interventions and the empowering of suicidal individuals to resist acting on their thoughts by increasing hopefulness, personal resilience and reasons for living (McLean 2008).…”
Section: Future Risk Factorsmentioning
confidence: 99%
“…Studies have identified training needs in the areas of control, sympathy and management which could improve relationships between nurses and patients (Cleary et al 2002;Markham 2003;James and Cowman 2007). The benefit of education was demonstrated in a study which used the self harm antipathy scale as a tool to show that after attending a twelve week course about self harm, negativity was reduced (Patterson et al 2007). However, in this study the course was optional which shows that those attending were already interested in the subject.…”
Section: Criterion -Borderline Personality Disordermentioning
confidence: 99%